Implementación de registros genealógicos de los cuatro biotipos de cerdos criollos que se encuentran en la Quinta Experimental Punzara - Torres Romero, Josselyne del Cisne (2024)
Genealogical records are documents or databases that contain information about ancestry and descent. The objective of this research was to implement genealogical records of the four biotypes of Creole pigs found in the Quinta Experimental Punzara of the National University of Loja. For its execution, we worked with the total population of Creole pigs from the year 2020 - 2023, distributed in four biotypes, 315 individuals in biotype I, 227 individuals in biotype II, 224 individuals in biotype III, 66 individuals in biotype IV, to determine consanguinity and kinship, the parents, first and second generation, were considered. The family tree was created with the data obtained from each biotype. The results were reported in the Excel spreadsheet and analyzed in the Pedigree Viewer program, in the four biotypes their consanguinity is zero in both the first and second generation, except in two families of biotype III of the first generation, I report the mating between own brothers, the progeny presented 25% consanguinity. In biotype I, II, III, IV kinship, it is 12.5% from grandparents to grandchildren, 25% from parents to children. Except in two consanguineous families of biotype III, the relationship is 37.5%, it is concluded that genealogical records of the four biotypes of Creole pigs must be carried out in order to control mating between close relatives that lead to an increase in consanguinity in the population.